Self‐reported cognition in older adults with insomnia: Associations with sleep and domain specific cognition. (11th October 2022) - Costa, Amy N.; Curtis, Ashley F.; Musich, Madison; Guandique, Alan A.; McCrae, Christina S.
Summary: Poor subjective evaluation of cognition and sleep are associated with cognitive decline in older adults. Relationships among self‐reported cognition, sleep, and cognitive domains remain unclear. We evaluated the interactive associations of objective cognition and subjective sleep with self‐reported cognition in older adults with insomnia. Fifty‐one older adults ( M age = 69.19, SD = 7.95) with insomnia completed 14 days of self‐reported cognition ratings (0‐very poor, 100‐very good), sleep (total sleep time (TST), sleep onset latency (SOL), wake after sleep onset (WASO), sleep efficiency), and daily cognitive tasks: Letter series (reasoning), word list delayed recall (verbal memory), Symbol Digit Modalities Test (SDMT) (attention/processing speed), and number copy (processing speed). Multiple regressions for each cognitive task determined whether average objective cognition or sleep were independently/interactively associated with average self‐reported cognition, controlling for age, education, and depression. The interaction between SDMT performance and TST was associated with self‐reported cognition. Specifically, the relationship between scores and self‐reported cognition was congruent in those with the shortest TST. Similarly, the interactions between SDMT and WASO, as well as sleep efficiency, were associated with self‐reported. Specifically, the relationship between scores and self‐reported cognition was congruent in those with longest and average WASO, as well as shortest and average sleep efficiency. The findings suggest, in an older adult population with insomnia, a congruent association exists between attention/processing speed and self‐reported cognition in those with worse subjective sleep (shorter TST, longer WASO, and lower SE). Insomnia symptoms should be taken into consideration when examining the relationship between objective cognition and self‐reported cognition.